2018
DOI: 10.1021/acs.macromol.8b00385
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effect on Strain Localizations in Glassy Polymer Films

Abstract: The physical properties of glassy polymer films change as they become confined. These changes are often attributed to increased average molecular mobility and reduction in entanglement density. Both are known to alter mechanical behavior, including the formation of strain localizations, e.g., crazing and shear deformation zones. Here, we determine how the entanglement density and surface mobility change the mechanical behavior of a glassy polymer film when it becomes confined. We utilize a custom-built uniaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(120 citation statements)
references
References 51 publications
15
105
0
Order By: Relevance
“…2C ). The measured moduli for polystyrene are comparable to literature values of bulk polystyrene specimens ( 32 , 33 ) and experimental values of thin films ( 16 , 34 , 35 ). The maximum stress σ Max for blends with ϕ > 0.80 is also approximately constant ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2C ). The measured moduli for polystyrene are comparable to literature values of bulk polystyrene specimens ( 32 , 33 ) and experimental values of thin films ( 16 , 34 , 35 ). The maximum stress σ Max for blends with ϕ > 0.80 is also approximately constant ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…However, linking these deformation mechanisms to the mechanical strength of a polymer glass is challenging since measurements of mechanical strength, such as the maximum failure stress or critical strain energy release rate, have been limited to thicker, bulk specimens where model polymer blends with controlled entanglements are challenging and cost prohibitive. In this study, we overcome this limitation by using a recently developed experimental method that allows measurement of the complete uniaxial stress-strain response of ultrathin polymer films ( 16 , 18 ). This approach allows us to systematically alter the state of entanglements using model polymer blends while also measuring their impact on mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…R ee ≈ 20 nm for the low M w PMMA and R ee ≈ 110 nm for the high M w PMMA based on an idealized equivalent freely jointed chain calculation [54]. This is in agreement with the results of Crosby and co-workers who conducted a series of uniaxial tensile tests on thin polystyrene (PS) films with M w = 136 000 g mol −1 [55,56]. They found that the tensile failure strain ε f decreases with decreasing film thickness t in the regime t = 15-77 nm; these values are close to the estimated value for R ee = 25 nm of the PS chains.…”
Section: Discussionsupporting
confidence: 87%
“…Although these models have been tested experimentally for characterizing the strength of a variety of materials with different shapes, such experimental validation has not been tested on ultrathin porous membranes. While there have been several notable studies that have investigated the mechanical characterization and tensile properties of non‐porous thin films, [ 52–55 ] we believe this is the first examination of the implications of introducing porosity in parylene nanomembranes. Previous studies on the mechanical properties of porous nanomembranes primarily used nanoindentation and bulge testing due to the challenge of conducting traditional tensile testing on ultrathin materials.…”
Section: Resultsmentioning
confidence: 99%